Components of essential oil of the Japanese mint 'Hokuto' and its deodorization effects against human malodors. Issue 6 (2nd November 2018) - Myoda, Takao; Matsumura, Takuma; Watanabe, Kensuke; Ebisuya, Koji; Kaneshima, Tai; Goto, Kotaro; Nojima, Satoshi; Hori, Yoji; Toeda, Kazuki; Nishizawa, Makoto; Fujimori, Takane
ABSTRACT: Japanese mint ( Mentha arvensis var. piperascens Malinv. ex Holmes), 'hokuto, ' is the highest-yield cultivar and contains a large amount of l -menthol in its essential oil. We focused on the dementholized oil of hokuto (hokuto DM oil), analysis of their aroma-active components and the potential deodorization effects against human malodors were demonstrated. The major components of hokuto DM oil were menthol, menthone, isomenthone and menthyl acetate. Among these, menthone, linalool, neoisomenthol, menthol and an unidentified compound were identified as the aroma-active components by AEDA. The deodorization activities of hokuto DM oil against four human malodors were measured by sensory evaluation and SPME-GC/MS analysis. Hokuto DM oil significantly deodorized isovaleric acid by a masking effect, with compounds containing a p -menthane skeleton, namely pulegone and menthone, found to contribute largely to the deodorant effects. These results demonstrate the possibility of using dementholized oil of Japanese mint as a freshening agent of toiletry products.